2019
DOI: 10.1016/j.heliyon.2019.e02293
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational culture on total quality management in SMEs in Nigeria

Abstract: The goal of this exploration is to observationally test the connection between total quality management and SMEs' performance. Specifically, it looks at whether organizational culture (OC) has an interceding impact on the TQM-SMEs performance relationship. Established on the literature review of TQM, OC and SMEs performance, the theoretical model for this investigation was formed. A self-controlled survey was utilized to gather information from the SMEs owners-managers in the South-western region of Nigeria. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 98 publications
(151 reference statements)
1
45
0
7
Order By: Relevance
“…Although there is a strengthening in environmental disclosure, it is not strong so it has no effect on financial performance. Based on these results, there must be indicators in the organizational culture that can influence environmental performance and disclosure strongly so that it can have a positive impact on financial performance such as the TQM in Nigerian SMEs (Eniola et al, 2019) and restaurants in the USA (Jogaratnam, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a strengthening in environmental disclosure, it is not strong so it has no effect on financial performance. Based on these results, there must be indicators in the organizational culture that can influence environmental performance and disclosure strongly so that it can have a positive impact on financial performance such as the TQM in Nigerian SMEs (Eniola et al, 2019) and restaurants in the USA (Jogaratnam, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, companies must implement these activities into an organizational culture. Organizational Culture applied by companies can increase company activities such as increasing accountability and efficiency in several childcare agencies (Vito, 2020), having a positive impact on TQM in SMEs (Eniola et al, 2019), and having a positive impact on restaurants in the USA (Jogaratnam, 2017). Based on the description, the third and fourth hypotheses to be tested are H3 = The effect of environmental performance on financial performance is strengthened by organizational culture as a moderating variable.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, a structural equation modeling (SEM) is developed to analyze operational communication. The choice of the tool was based on its use in recent research in organizational studies, for example [6,27,57,91,92]: the effect of internal communication and worker satisfaction on the integration in the shop floor; investment in intellectual capital and knowledge management; security climate; human resources management; and organizational culture.…”
Section: Methodsmentioning
confidence: 99%
“…It could be observed that several studies have provided significant outcomes in enhancing SMEs' performance in developing countries (Alosani et al, 2020;Bahta et al, 2020;Eniola et al, 2019;Kiyabo & Isaga, 2019). However, few studies provide effective antecedents, variables, and models that impact SMEs' performance, leading to their weak performance in developing countries (G. , particularly in Kuwait (Abu-Aisheh, 2018;Al-duwailah et al, 2019;Alzougool, 2019).…”
Section: Organizational Performancementioning
confidence: 99%